Υγεία και ασφάλεια των εργαζομένων: όχι χωρίς την επιθεώρηση εργασίας - Μέκος, Κωνσταντίνος Ζ. (SPOUDAI Journal of Economics and Business, 2006)
This article examines the obstacles encountered when one litigates in order to receive compensation for an occupational injur}' or disease. These obstacles are related with the financial capabilities of companies and workers, the legal procedure and the retardation in adjudicating, as well as the uncertainty which is innate in litigation. Therefore, the necessity of having a special legislation enforced by an inspecting mechanism arises. The article also explicates the advantages a civil service labour inspectorate offers and the impossibility of substituting a private company for such a civil service. Finally, the article presents the characteristics of the Greek labour inspectorate. JEL Classifications: J28, Η11, D73